(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study aims to (1) identify and analyze the nature of real estate consumer legal protection from developers, (2) identify and analyze the effectiveness of real estate consumer legal protection, (3) analyze and explain the factors that influence real estate consumer legal protection for the fulfilment of facilities housing promised by the developer in the province of Central Sulawesi. This research uses philosophical research types of legal research, normative legal research and socio-legal research by using quantitative techniques on data sourced from primary and secondary data by analyzing the substance of real estate consumer legal protection by using juridical requirements as benchmarks and the hypothesis is tested using frequency distribution and multiple regression. The results of this study indicate that: the nature of real estate consumer protection provides guarantees for certainty of rights, social justice, harmony/peace, benefit, and balance to consumers, which form the basis of Law No. 1 of 2011 concerning housing and settlements, but empirically it has not been fully implemented correctly and responsibly by developers in Central Sulawesi Province. The effectiveness of legal protection for real estate consumers in fulfilling housing facilities promised by developers in Central Sulawesi Province empirically cannot be implemented properly and responsibly. Factors that influence real estate legal protection are supervision, developer legal awareness, real estate consumer legal awareness, facilities and infrastructure, and the implementation of sanctions; the most important factors influencing legal protection are legal oversight factors from the government, developers and real estate consumers.